Holistic organizaational transformation and dual-mode innovation culture: Explaining apple's strategic marketing success and sustainability - Muslim, Aini Khalida; Mohd Tan, Athirah; Ahmad, Naveed; Ishak, Muhamad Izaidi; Govinda Raj, Vimala; Mohd Dzulkifli, Dzunnur Zaily (Research and Scientific Innovation Society, 2025)
This theoretical paper has explored how the organizational change in Apple Inc. in terms of leadership, corporate culture, operations, marketing and human resource management led to its long-term competitive advantage. Despite the large body of research on Apple in terms of innovation and branding, previous research studies had hardly combined internal variables into a single theoretical framework, which made a gap in the conceptualization of how cross-functional change influenced the long-term marketing performance. To surmount this shortcoming, the paper has synthesized recent works in the literature of strategies management, organizational behavior and marketing to create a holistic framework, which interpreted how Apple changed its leadership with a personality to a process-driven stability, how it has created a hybrid culture of secrecy and collaboration, and how it has transformed its supply chain and human resource. The synthesis showed that all these combined improvements contributed to the Apple innovation capability, creation of customer value, and market resilience, and new challenges, including competitive pressure, privacy concerns, intellectual property debate, supply chain ethics, and sustainability pressures were still affecting the strategic direction of the company. The innovation of the paper was the cross-functional transformation lens and new constructs such as leadership continuity transformation and ethical branding misalignment supply chain. The research paper was meant to contribute to the conceptual knowledge of organizational change and its meaning to the researcher studying strategic change in international technology companies.